Efficacy and mucosal toxicity of concomitant chemo-radiotherapy in patients with locally-advanced squamous cell carcinoma of the head-and-neck in the light of a novel mathematical model. (June 2016) - Strigari, Lidia; Pinnarò, Paola; Carlini, Paolo; Torino, Francesco; Strolin, Silvia; Minosse, Silvia; Sanguineti, Giuseppe; Benassi, Marcello
Highlights: EQD2 and the type of CT, the chemo-sensitization fraction and HPV status as significant prognostic factors of 5y-OS. EQD2 and the concomitant administration of Fu resulted as significant prognostic factors of toxicity. The outcome of 2785 patients from 9 randomized trials has been investigated. Multivariate logistic regression models can be used to predict the outcome after CRT in LA-HNSCC. Abstract: Background: In the last several decades, combined radiotherapy (RT) and chemotherapy (CT) have been recognized as feasible in locally-advanced-squamous-cell-carcinoma of the head-and-neck (LA-HNSCC). Several meta-analyses identified concurrent RT + CT (CRT) most likely effective approach respect to RT-alone. However, radiobiological models comparing different chemotherapeutic schedules against delivered RT fractionation schedule for overall survival and toxicity are still needed. Methods and materials: Based on 9 randomized trials (2785 patients), radiobiological models and multivariate logistic regression model were used to derive dose-response curves and estimate the 5-year-overall survival (OS) and ≥G3 acute mucositis rate of CRT or RT-alone. Results: Equivalent dose at 2 Gy/fraction (EQD2) was calculated using the linear quadratic model. The effect of CRT schedules, considering the CT type and its administration schedule and the HPV status of tumors were estimated using the univariate/multivariate logistic regression. The multivariate logistic regression model for 5y-OS indicated EQD2 and the type of CT, the chemo-sensitization fraction and the HPV status significant prognostic factors, while for toxicity both EQD2 and the concomitant administration of 5-fluorouracil (5Fu) resulted as significant prognostic factors. Combined schedules cisplatin (DDP)+/−5Fu + RT produced the higher OS compared with combined carboplatin+/−5Fu + RT or RT-alone. The concomitant administration of Fu and schedule with high EQD2 increase the rate of observed ≥G3 acute mucositis. Conclusion: Multivariate logistic regression models can be used to predict CRT effect in terms of OS and ≥G3-mucositis, contributing to the identification of novel treatment schedules.